New methods of increasing transparency: Does viewing webcam pictures change peoples' opinions towards modern pig farming? - Sarah Gauly; Andreas Müller; Achim Spiller (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2017)
Public interest in livestock farming is increasing, as is general criticism regarding the welfare of farm animals. In this context, husbandry systems for pigs especially are perceived very negatively. Despite rising concern for animal farming, most people lack detailed knowledge of modern agricultural production processes, as well as direct contact with agriculture. With regards to public demand for transparency of production quality and animal welfare standards, farmers and farmer associations in several countries have begun installing webcams in dairy, pig and poultry farming operations. Along with informational texts, pictures from webcams are publicly available on the internet and are used as a new type of communication tool aimed at increasing the acceptance of livestock farming by providing farming-specific information. However, there are currently no existing studies quantitatively investigating the effect of webcam pictures from stables and accompanying informational texts on the broader public. In a randomized between-subject experimental design, we presented two webcam pictures from conventional pig barns (pig fattening barn and sow farrowing pen) to the broader public, along with two different informational texts (one written directly by farmers and one neutrally written by the authors). Therefore, the objective of this study is to examine 1) if the attitude towards pig farming changes after having seen the webcam pictures, 2) if different informational texts alter the evaluation of webcam pictures, 3) if there are differences in the perception of webcam pictures of a pig fattening barn and a sow farrowing pen, and 4) how people evaluate the use of webcams as a public relations tool that can be used to provide transparency. It was determined that the majority of respondents display a more negative attitude after viewing the webcam pictures and informational texts, and this is especially true for participants reading the neutrally written texts. Further, the farrowing pen is evaluated substantially more negatively than the pig fattening pen. Regarding the overall evaluation of webcams, people seem to appreciate that farmers show real pictures from their stables, although a rather low interest in the usage of webcams in agriculture can be observed. Thus, although transparency may be enhanced through the use of webcams, our findings suggest that webcams generally do not show the desired effects on the public and are likely to be unable to improve the image of pig farming by simply providing information via pictures and texts. Finally, the application of webcams as a communication tool cannot be recommended, at least not for the husbandry systems investigated within this study.
Keywords: 330; pig farming; webcam; transparency; attitude change; image; communication tool